Answer:
![9 + \frac{n}{3} - 6 = 7](https://tex.z-dn.net/?f=9%20%2B%20%5Cfrac%7Bn%7D%7B3%7D%20-%206%20%3D%207)
Step-by-step explanation:
Given
![9 + \frac{n}{3} - 6](https://tex.z-dn.net/?f=9%20%2B%20%5Cfrac%7Bn%7D%7B3%7D%20-%206)
Required
Evaluate when n = 12
Substitute 12 for n in ![9 + \frac{n}{3} - 6](https://tex.z-dn.net/?f=9%20%2B%20%5Cfrac%7Bn%7D%7B3%7D%20-%206)
![9 + \frac{n}{3} - 6 = 9 + \frac{12}{3} - 6](https://tex.z-dn.net/?f=9%20%2B%20%5Cfrac%7Bn%7D%7B3%7D%20-%206%20%3D%209%20%2B%20%5Cfrac%7B12%7D%7B3%7D%20-%206)
Simplify the fraction
![9 + \frac{n}{3} - 6 = 9 + 4 - 6](https://tex.z-dn.net/?f=9%20%2B%20%5Cfrac%7Bn%7D%7B3%7D%20-%206%20%3D%209%20%2B%204%20-%206)
![9 + \frac{n}{3} - 6 = 7](https://tex.z-dn.net/?f=9%20%2B%20%5Cfrac%7Bn%7D%7B3%7D%20-%206%20%3D%207)
Answer:
It will take 3.214 minutes.
Step-by-step explanation:
<em>It is given that, the conveyor belt transports 300 cans in 5 mins and the smaller belt transports 300 cans in 9 minutes.</em>
Thus , the speed of conveyor belt is,
= ![\frac{300}{5} = 60 cans per minute](https://tex.z-dn.net/?f=%5Cfrac%7B300%7D%7B5%7D%20%3D%2060%20cans%20per%20minute)
and of smaller belt is,
= ![\frac{300}{9} = \frac{100}{3} cans per minute](https://tex.z-dn.net/?f=%5Cfrac%7B300%7D%7B9%7D%20%3D%20%5Cfrac%7B100%7D%7B3%7D%20cans%20per%20minute)
Thus, when both are used together,
<em>conveyor belt will transport (60)(t) cans and smaller belt will transport
(t) cans per minute.</em>
Thus the equation becomes,
![300 = (60)(t) + (\frac{100}{3})(t) = (\frac{280}{3})(t)](https://tex.z-dn.net/?f=300%20%3D%20%2860%29%28t%29%20%2B%20%28%5Cfrac%7B100%7D%7B3%7D%29%28t%29%20%3D%20%28%5Cfrac%7B280%7D%7B3%7D%29%28t%29)
t = ![\frac{(300)(3)}{280} = \frac{45}{14} = 3.214 minutes](https://tex.z-dn.net/?f=%5Cfrac%7B%28300%29%283%29%7D%7B280%7D%20%3D%20%5Cfrac%7B45%7D%7B14%7D%20%3D%203.214%20minutes)
<h2>218 = 49 + 169 = 7² + 13² </h2><h2><u>218 = 7² + 13²</u> </h2><h2> </h2><h2> </h2><h2> </h2><h2 />
Answer:
Step-by-step explanation:
(i) x+2y=4
(ii) x=4-2y
(iii) 2x-2y=5
substituting (ii) in (iii)
2x-2y=5
2(4-2y)-2y=5
8-4y-2y=5
-6y=5-8
-6y=-3
(iv) y=
substituting (iv) in (ii)
x=4-2y
x=4-2×![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
x=4-1
x=3
∴ B.(3,
)
HOPE IT HELPS YOU!!!!
A,b,d,e,f,h would be similar because they are all quadrilaterals (they all have four sides) and c,g would be the same because they are both triangles